(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1865)
The author explains the two different types of chambered cairn found in Caithness: round and long cairns. He goes on to describe two long cairns at Thrumster that were recently excavated including their size and shape, their internal layout, and the finds that were discovered in each cairn. These cairns are then compared to the cairns at Ormiegill and Camster, also in Caithness. He concludes that it is too early in the study of these sites to confidently assess when they were built or their significance.